Atherosclerotic cardiovascular diseases in inflammatory bowel diseases: to the heart of the issue - Gabbiadini, Roberto; Dal Buono, Arianna; Mastrorocco, Elisabetta; Solitano, Virginia; Repici, Alessandro; Spinelli, Antonino; Condorelli, Gianluigi; Armuzzi, Alessandro (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerotic cardiovascular disease and stroke are the leading causes of morbidity and mortality worldwide. Along to the traditional risk factors for these diseases, chronic inflammation is known to be an important player in accelerating the process of atherosclerosis, which can result in an increased incidence of arterial thromboembolic events. As in other chronic inflammatory diseases, in the past few years, several studies suggested that subjects affected by inflammatory bowel diseases (IBD) may also be at an incremented risk of atherosclerotic disease, especially during the periods of disease's flare. Therefore, IBD treatment may assume an important role for achieving both disease remission and the control of the atherosclerotic risk. In this article we aimed to perform a comprehensive review on evidence on the increased risk of arterial thromboembolic events in patients affected by IBD and discuss the potential role of IBD therapy in reducing this risk.